Synthesis, Crystal Structure, and Hydrogen Bonding of μ-Hydroxo-μ-peroxo-bis[bis(ethylenediamine)cobalt(III)] Squarate - Köferstein, Roberto; Robl, Christian (Zeitschrift für anorganische und allgemeine Chemie (1950), 2016)
Black‐brown needle‐shaped single crystals of [Co2(en)4(O2)(OH)][C4O4]1.5·4H2O (en = ethylenediamine) were prepared in aqueous solution at room temperature [space group P$\bar{1}$ (no.2) with a = 800.20(8), b = 1225.48(7), c = 1403.84(9) pm, α = 100.282(5), β = 94.515(7), and γ = 95.596(6)°]. The Co3+ cations [Co(1), Co(2)] are coordinated in an octahedral manner by four nitrogen atoms stemming from the ethylenediamine molecules and two oxygen atoms each from a hydroxo group and a peroxo group, respectively. Both Co3+ coordination polyhedra are connected by a common corner and by the peroxo group leading to the dinuclear [(en)2Co(O2)(OH)Co(en)2]3+ cation. The squarate dianions, not bonded to Co3+, and the [(en)2Co(O2)(OH)Co(en)2]3+ cations are linked by hydrogen bonds forming a three‐dimensional supramolecular network containing water molecules. Magnetic measurements revealed a diamagnetic behavior indicating a low‐spin electron configuration of Co3+. The UV/Vis spectra show two LMCT bands [π*(O22–) → dσ*(Co3+)] at 274 and 368 nm and the d–d transition (1A1g → 1T1g) at 542 nm. Thermoanalytical investigations in air show that the compound is stable up to 120 °C. Subsequent decomposition processes to cobalt oxide are finished at 460 °C.